Project-KOMPLIT learning model (computational, creative, and literacy) in science education elementary school - Kumala, Farida Nur (Education and Development Research, 2025)
The purpose of this study was to develop a Project KOMPLIT learning model (computational, critical, creative thinking, and literacy for elementary school students) in science education in elementary schools and to test the validity of the model that has been developed. The method used in this study is the development of ADDIE, with the research subjects being experts in elementary school science learning materials, models and languages, and practical tests for teachers, the instruments used in this study were test instruments, observations and questionnaires that included questionnaires assessing learning models, language and materials used. The data analysis techniques used in this study were quantitative and qualitative data analysis techniques. The results of the study showed that the results of the needs analysis showed that most of the research on student computational, creative and literacy still needed to be improved so that the development of a learning model was needed. The learning model developed consisted of five steps based on complete thinking skills (Computational, critical, creative, and literacy) for elementary school students. The results showed that subject matter experts gave an assessment of 88%, learning model experts 90%, language experts 93% and the teacher 89%. The developed model is equipped with a teaching model book. Based on the results of the model development, it is known that the learning model is worthy of further testing in the student learning process to improve computational skills, creative thinking, and literacy in elementary school science education.